Impact of roux‐en Y gastric bypass surgery on prognostic factors of type 2 diabetes mellitus: meta‐analysis and systematic review. Issue 7 (17th December 2014) - Chen, Yali; Zeng, Guangzheng; Tan, Jingwang; Tang, Jun; Ma, Jingsheng; Rao, Benqiang
Summary Our aim is to clarify the features of complete type 2 diabetes mellitus (T2DM) remission in patients who undergo Roux‐en Y gastric bypass surgery, to better determine factors affecting the outcome of T2DM surgery. A search was conducted for original studies on Medline, PubMed and Elsevier from inception until October 28, 2014. All of the articles included in this study were assessed with the application of predetermined selection criteria and were divided into two groups: Roux‐en Y gastric bypass surgery for T2DM patients in remission or non‐remission. The meta‐analysis results demonstrated that fasting C‐peptide values were significantly associated with increased remission (C‐peptide: 95%CI = 0.2–1.0) whereas T2DM duration, patient age, preoperative insulin use, preoperative fasting blood glucose values and preoperative glycosylated haemoglobin values were significantly associated with reduced remission (T2DM duration: 95%CI = −1.2 – −0.7; age: 95%CI = −0.5 – −0.1; percentage of preoperative insulin users: odd ratio = 0.10, 95%CI = 0.07–0.15; preoperative fasting blood glucose: 95%CI = −0.9 – −0.5; preoperative glycosylated haemoglobin: 95%CI = −1.1 – −0.4). However, the results demonstrated that body mass index was not statistically different (body mass index: 95%CI = −0.2–0.6). The results of the systematic review demonstrated that smaller waist circumference; lower total cholesterol, triglycerides and low‐density lipoprotein levels, increased higher high‐density lipoprotein levels, shorter cardiovascular disease history and less preoperative prevalence of hypertension contribute to the increased postoperative remission rate. Better results are obtained in younger patients with less severe diabetes, a smaller waist circumference, higher preoperative high‐density lipoprotein, lower preoperative total cholesterol, triglycerides and low‐density lipoprotein levels and fewer other complications of shorter durations. Copyright © 2014 John Wiley & Sons, Ltd.